Assessing acute responses to exercises performed within and at the upper boundary of severe exercise domain - Norouzi, M.; Cabuk, R.; Balci, G. A.; As, H.; Ozkaya, O. (Research Quarterly for Exercise and Sport, 2023)
Purpose: The highest work-rate that provides maximal oxygen uptake (VO2max) may be one of the best exercise stimuli to yield both VO2max and lactate accumulation. The aim of this study was to analyze physiological and metabolic acute responses of an exercise modality performed at the upper boundary of the severe exercise domain, and compare those responses with exercise modalities applied within the severe exercise domain.